Husband and Family Support in Postpartum Depression Mothers at PDHI Yogyakarta Islamic Hospital - Sugiyanti, Rina; Nurfaizah, Astriani; Kadarmo, Aji (Universitas Ahmad Dahlan, 2023)
Postpartum depression (PPD) is a psychological illness that affects mothers after giving birth and can last for up to two years. Its symptoms include sadness, anger, fatigue, loneliness, feeling undervalued, and even thoughts of suicide or harming others. These circumstances may harm the mother, impede the growth of the child, and have an impact on the mother's family, needing help from the husband and family. This study at the PDHI Yogyakarta Islamic Hospital intends to ascertain the association between husband and family support and the prevalence of PPD. This research is a quantitative study that uses an observational-analytical method with a cross-sectional design. The sample was taken using probability sampling techniques, resulting in 29 postpartum mothers as participants. The Edinburgh Postnatal Depression Scale (EPDS) questionnaire is used to identify PPD symptoms. The results of the study showed that out of the 29 samples, 14 mothers experienced PPD (48.3%). The percentage of mothers who did not receive husband support was 20.3%, and those who did not receive family support was 13.8%. Bivariate analysis using the Fisher’s Exact Test showed a p-value of 0.006 for husband support and a p-value of 0.042 for family support. These values are considered valid because p < α (0.05). Thus, it can be concluded that there is a relationship between husband and family support with PPD incidence in postpartum mothers at PDHI Yogyakarta Islamic Hospital.